Urban-rural differences in diabetes in China: Reply - Bragg, F; Li, L; Chen, Z (American Medical Association, 2017)
In Reply: The China Kadoorie Biobank (CKB) was not designed to be nationally representative, and the 10 study areas were selected from different provinces to capture the diversity of populations in China. Diabetes prevalence in the CKB (5.9%) was lower than in some more recent studies,1,2 possibly reflecting increasing temporal trends in diabetes prevalence in China and also the different methods used for diagnosing diabetes in different studies.